Needs and Preferences of Qur‟anic Arabic Vocabulary Learners Regarding Learning through Qur‟anic Arabic Mobile Applications - F., Y. Mustaffa; A., R. Salam; N.H., Mohd Sharif; A. , Sirri; A.H. , Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
This preliminary research intends to discover the needs and preferences of Qur’anic Arabic learners regarding learning Qur’anic Arabic vocabulary through mobile applications. Specifically, we would like to identify what features are required by Qur’anic Arabic vocabulary learners in a Qur’anic Arabic vocabulary mobile application in order for them to be able to learn Qur’anic Arabic vocabulary effectively. This study uses the phenomenology research design with semi-structured interviews as data-gathering instruments. The collected data were analyzed in Nvivo 12 Plus software using thematic analysis. The findings from this study indicated that novice learners need to learn vocabulary items, have access to the tafseer of the word or verse being studied, and be given ample vocabulary exercises so that they can internalize the vocabulary items being studied. Added to this, vocabulary items contained in Juz 30 of the Qur’an should be emphasized due to their familiarity with them (for recitation in their daily salaah). As for their preferences, they would like the app to be interactive, be equipped with progress indicators, and preferably include audio of the pronunciation of the studied vocabulary item. Learners are also willing to spend from thirty minutes to an hour in one sitting. For advanced learners, lessons on grammatical inflection analysis or I’rab should be given for them to advance further in Qur’anic Arabic learning.